PKA inhibition is a central step in D,L-methadone-induced ER Ca2+ release and subsequent apoptosis in acute lymphoblastic leukemia - Kamran, Hamza; Lee, Jung Kwon; Lee, Ki-Young (Frontiers in Cell and Developmental Biology, 2024)
Acute lymphoblastic leukemia (ALL) is a hematologic cancer that mostly affects children. It accounts for over a quarter of ALL pediatric cancers, causing most of the cancer death among children. Previously, we demonstrated that D,L-methadone causes ALL cell apoptosis via μ-opioid receptor 1 (OPRM1)-triggered ER Ca2+ release and decrease in Ca2+ efflux, elevating [Ca2+]i. However, the precise mechanism by which D,L-methadone induces ER Ca2+ release remains to be defined. Here, we show that in ALL cells, D,L-methadone-induced ER Ca2+ release is blocked by inhibition of Gαi, but not Gβϒ, indicating that the process is dependent on Gαi. Activation of adenylyl cyclase (AC) with forskolin or treatment with 8-CPT-cAMP blocks D,L-methadone-induced ER Ca2+ release, indicating that the latter results from Gαi-dependent downregulation of AC and cAMP. The 14–22 amide (myr) PKA inhibitor alone elicits ER Ca2+ release, and subsequent treatment with D,L-methadone does not cause additional ER Ca2+ release, indicating that PKA inhibition is a key step in D,L-methadone-induced ER Ca2+ release and can bypass the D,L-methadone-OPRM1-AC-cAMP step. This is consistent with the decrease in PKA-dependent (i) inhibitory PLCβ3 Ser1105 phosphorylation that leads to PLCβ3 activation and ER Ca2+ release, and (ii) BAD Ser118 phosphorylation, which together ultimately result in caspase activation and apoptosis. Thus, our findings indicate that D,L-methadone-induced ER Ca2+ release and subsequent apoptosis in ALL cells is mediated by Gαi-dependent downregulation of the AC-cAMP-PKA-PLCβ3/BAD pathway. The fact that 14–22 amide (myr) alone effectively kills ALL cells suggests that PKA may be targeted for ALL therapy.